Quality of life in hematopoietic stem cell transplantation during the Covid-19 pandemic: case series - Oshiro, Natália Naome; Nogueira, Luciana de Alcantara; Marcon, Sonia Silva; Silva, Leonel dos Santos; Miranda, Amanda Gomes de; Guimarães, Paulo Ricardo Bittencourt; Kalinke, Luciana Puchalski (O Mundo da Saúde, 2024)
Hematopoietic Stem Cell Transplantation is a complex treatment, aimed at curing malignant and benign diseases, which directly affects the quality of life of patients and caregivers. Studies prior to the pandemic period presented aspects of caregiver burden and quality of life for both; this current research contributes to this gap on the topic during the pandemic. To evaluate and correlate the quality of life of hematopoietic stem cell transplant recipients with the quality of life and caregiver burden during the COVID-19 pandemic. Case series with 16 dyads, carried out in a public hospital in Brazil, a reference in Latin America. The quality of life of transplant recipients was assessed with the Functional Assessment Cancer Therapy-Bone Marrow Transplantation, caregivers with the Medical Outcomes Studt 36-Item Short Form Health Survey, burden with the Zarit Burden Interview. There was a lower perception of the functional well-being of transplant recipients and a worse general health status of caregivers; the caregiver's mental health interfered in different domains of quality of life; there was a negative correlation between quality of life and caregiver burden. The pandemic impacted the dyads’ quality of life; there is a need for additional support for both the patient and the caregiver.